Análise microbiológica e físico-química da água de poços artesianos que abastecem moradores da zona rural do município de Itabaiana, Sergipe - Anjos, Daianne Santos dos (2023)
Water is an essential element for the survival of all species, including humans, so the conservation of this natural element is essential. Several industrial and agricultural activities make use of water with disorderly consumption. Due to the lack of potable water, groundwater appears as an alternative source for human consumption, mainly through the drilling of tubular artesian wells. For this reason, the objective of this research was to analyze, through microbiological and physical-chemical parameters, the quality of water from artesian wells that supply the rural area of the municipality of Itabaiana, state of Sergipe. The present study is a descriptive, exploratory and quantitative research. In this sense, nineteen public wells were selected to compose the sample for this research. The collection for microbiological analysis of water samples was carried out in nineteen wells, while the collection for the physicalchemical parameters was carried out in nine wells, in order to verify its potability for human consumption. After carrying out the analyses, the results were related to the parameters of the legislation that regulates the potability of water Ordinances of the Ministry of Health nº 2.914/11, nº 888/21. The microbiological results showed the presence of Escherichia coli in nine wells, in addition to the detection of heterotrophic bacteria in three wells. As for the physical-chemical results, the maximum values allowed by legislation were obtained for the parameters of electrical conductivity in eight wells, Hardness in three wells, Chlorides in five wells, Alkalinity in six wells and Free residual chlorine. with the minimum values allowed by legislation 888/21, which indicates that the minimum value of residual chlorine is 0.5 mg L -1. Regarding the parameters of Temperature and Hydrogenionic Potential (pH), all analyzed points are in compliance with the legislation. It is important to emphasize that, during the collections, it was observed that on the margins of these contaminated wells there was the insertion of garbage, cattle raising, in addition to open sewers. All these factors mentioned contribute significantly to the proliferation of these pathogenic microorganisms in water, in addition to putting the health of the population that ingests contaminated water at risk.